Expression of Apoptosis‐regulating Proteins Bcl‐2 and Bax in Lymph Node Aspirates from Dogs with Lymphoma. (25th March 2016) - Meichner, K.; Fogle, J.E.; English, L.; Suter, S.E.
Abstract : Background: Dysregulated apoptosis is a hallmark of tumorigenesis, and is also involved in resistance to cytotoxic treatment, and might be relevant in lymphoma in dogs. Hypothesis/Objectives: That Bcl‐2/Bax expression patterns differ between lymphoma immunophenotypes, and that Bcl‐2/Bax ratio is correlated with prognosis. Animals: Fifty‐five client‐owned dogs with multicentric lymphoma and 5 healthy dogs. Methods: Prospective, case–control study. We compared 3 methods (flow cytometry, qRT‐PCR, Western blot) for Bcl‐2 and Bax quantification in a subset of dogs. The effect of time on Bcl‐2/Bax ratios measured by flow cytometry was assessed in lymphoma cell lines. Immunophenotype and Bcl‐2/Bax expression by flow cytometry were determined in LN aspirates from all dogs with multicentric lymphoma compared to healthy dogs. Progression‐free survival (PFS) was retrospectively evaluated in a group of dogs all receiving similar treatment. Results: Bcl‐2/Bax ratios remain consistent for at least 5 days after sample collection. Bcl‐2/Bax ratio was higher in dogs with T‐cell lymphoma (TCL; median 0.97, range 0.37–1.36) compared to B‐cell lymphoma (BCL; median 0.36, range 0.07–1.45) ( P < .0001) and normal dogs (median 0.36, range 0.21–0.48) ( P = .0006), respectively. Dogs with Bcl‐2/Bax ratios higher than the median of the group experienced a median PFS of 101 days and dogs with ratios equal and lower than the median had PFS of 130 days ( P = .19). Conclusions and clinical importance: Higher intrinsic resistance to apoptosis following cytotoxic treatment might contribute to the less favorable prognosis associated with multicentric TCL in dogs. Whether Bcl‐2/Bax will be helpful to identify canine BCL and TCL with more aggressive and more indolent behavior, respectively, should be evaluated in larger prospective clinical studies.